Relationship between Antibiotic Consumption and Resistance: A Systematic Review - Asrat Agalu Abejew; Gizachew Yismaw Wubetu; Teferi Gedif Fenta (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Unreserved use of antibiotics exerted selective pressure on susceptible bacteria, resulting in the survival of resistant strains. Despite this, the relationship between antibiotic resistance (ABR) and antibiotic consumption (ABC) is rarely studied. This systematic review aims to review the relationship between ABC and ABR from 2016 to 2022. Methods. Articles published over 7 years (2016–2022) were searched from December 23 to 31, 2022. The search strategy was developed by using keywords for ABC and ABR. From 3367 articles, 58 eligible articles were included in the final review. Results. The pooled ABC was 948017.9 DPDs and 4108.6 DIDs where over 70% of antibiotics were from the Watch and Reserve category based on the WHO AWaRe classification. The average pooled prevalence of ABR was 38.4%. Enterococcus faecium (59.4%), A. baumannii (52.6%), and P. aeruginosa (48.6%) were the most common antibiotic-resistant bacteria. Cephalosporins (76.8%), penicillin (58.3%), and aminoglycosides (52%) were commonly involved antibiotics in ABR. The positive correlation between ABR and consumption accounted for 311 (81%). The correlation between ABR P. aeruginosa and ABC accounted for 87 (22.7%), followed by 78 (20.3%) and 77 (20.1%) for ABR E. coli and K. pneumoniae with ABCs, respectively. Consumption of carbapenems and fluoroquinolones was most commonly correlated with resistance rates of P. aeruginosa, K. pneumoniae, E. coli, and A. baumannii. Conclusion. There is a positive correlation between ABC and the rate of ABR. The review also revealed a cross-resistance between the consumption of different antibiotics and ABR. Optimizing antibiotic therapy and reducing unnecessary ABC will prevent the emergence and spread of ABR. Thus, advocating the implementation of stewardship programs plays a pivotal role in containing ABR.